Analysis of critical and semi-critical factors in waste management in a blood center in Northeastern Brazil (Research, Society and Development, 2021)
The incorrect handling and disposal of  Health Service Waste (HSW) can cause flooding, significant water accumulation and the appearance of disease-transmitting vectors. HSW are produced in hospitals, blood centers, laboratories, offices, among others. The objective was to verify the critical and semi-critical factors in the management of waste in a Hemocenter in the Northeast of Brazil. This is a qualitative, descriptive and exploratory study. A semi-structured questionnaire was used to assess the management system, the management of common, biological and chemical waste, segregation, identification, conditioning, collection and internal transport, external storage, its treatment and disposal. The situational diagnosis found the critical and semi-critical factors in waste management in the study scenario. As for the critical factors corresponding to the environmental aspects, 40% complied with the standards with restrictions, being the liquid effluents and the management system, while 60% complied with the recommended laws, which are the common, chemical and biological residues. As for the management of waste in the case of critical factors, 66.6% did not meet the current standards. There was a need for the implementation of appropriate procedures, as well as permanent education in health services, involving professionals, with the aim of adapting the management of waste and processes, regarding the improvement in physical infrastructure related to internal and external shelter of HSW, aiming at guaranteeing sufficient space and minimizing risks of contamination of people and the environment. The data obtained showed satisfactory results for the institution regarding the disposal of HSW.